Suppressors of Cytokine Signaling (SOCS)1 and SOCS3 Proteins Are Mediators of Interleukin-10 Modulation of Inflammatory Responses Induced by Chlamydia muridarum and Its Major Outer Membrane Protein (MOMP) in Mouse J774 Macrophages - Skyla A. Duncan; Rajnish Sahu; Saurabh Dixit; Shree R. Singh; Vida A. Dennis (Mediators of Inflammation)
The immunopathology of chlamydial diseases is exacerbated by a broad-spectrum of inflammatory mediators, which we reported are inhibited by IL-10 in macrophages. However, the chlamydial protein moiety that induces the inflammatory mediators and the mechanisms by which IL-10 inhibits them are unknown. We hypothesized that Chlamydia major outer membrane protein (MOMP) mediates its disease pathogenesis, and the suppressor of cytokine signaling (SOCS)1 and SOCS3 proteins are mediators of the IL-10 inhibitory actions. Our hypothesis was tested by exposing mouse J774 macrophages to chlamydial stimulants (live Chlamydia muridarum and MOMP) with and without IL-10. MOMP significantly induced several inflammatory mediators (IL-6, IL-12p40, CCL5, CXCL10), which were dose-dependently inhibited by IL-10. Chlamydial stimulants induced the mRNA gene transcripts and protein expression of SOCS1 and SOCS3, with more SOCS3 expression. Notably, IL-10 reciprocally regulated their expression by reducing SOCS1 and increasing SOCS3. Specific inhibitions of MAPK pathways revealed that p38, JNK, and MEK1/2 are required for inducing inflammatory mediators as well as SOCS1 and SOCS3. Chlamydial stimulants triggered an M1 pro-inflammatory phenotype evidently by an enhanced nos2 (M1 marker) expression, which was skewed by IL-10 towards a more M2 anti-inflammatory phenotype by the increased expression of mrc1 and arg1 (M2 markers) and the reduced SOCS1/SOCS3 ratios. Neutralization of endogenously produced IL-10 augmented the secretion of inflammatory mediators, reduced SOCS3 expression, and skewed the chlamydial M1 to an M2 phenotype. Inhibition of proteasome degradation increased TNF but decreased IL-10, CCL5, and CXCL10 secretion by suppressing SOCS1 and SOCS3 expressions and dysregulating their STAT1 and STAT3 transcription factors. Our data show that SOCS1 and SOCS3 are regulators of IL-10 inhibitory actions, and underscore SOCS proteins as therapeutic targets for IL-10 control of inflammation for Chlamydia and other bacterial inflammatory diseases.